E-scooter attitudes and risk-taking behaviours: an international systematic literature review and survey responses in the West Midlands, United Kingdom - Nathalie Burt; Nathalie Burt; Zubair Ahmed; Zubair Ahmed; Zubair Ahmed (Frontiers Media S.A., 2023)
IntroductionMicromobility initiatives, including electric scooters (e-scooters), are part of the United Kingdom government's sustainability drive. Since summer 2020, multiple trials have been conducted across the United Kingdom. Safety concerns have been raised around e-scooters joining other vehicles on United Kingdom roads, alongside the numerous private e-scooters illegally ridden on public land. Although literature has been published abroad on perceptions, risk-taking behaviours and attitudes surrounding e-scooters, independent United Kingdom research has concentrated on analysing trauma. Our aim was to identify common themes and recommendations to form conclusions on factors affecting e-scooter trauma hospital admissions.MethodsA systematic literature search in June 2023 extracted studies focused on the primary outcomes of risk factors, perceptions, and attitudes surrounding e-scooters globally from the EMBASE, PubMed, and Web of Sciences databases. Two independent reviewers conducted a critical appraisal to extract potential biases and study characteristics. A critical appraisal skills programme (CASP) analysis was also completed. Two online surveys distributed in Birmingham and Wolverhampton focused on: public perception towards e-scooters, and road user attitudes around e-scooters. The target population was residents of the West Midlands who were both riders and non-riders of e-scooters. The surveys were opened in late-March 2023 and closed in late-July 2023.Results443 studies were retrieved with 13 studies being eligible according to our inclusion and exclusion criteria. CASP assessment concluded that the studies were of good quality, however heterogeneity meant sample sizes could not be meaningfully aggregated. Many studies focused on safety concerns whilst others observed risk-taking behaviour, non-rider perceptions, and infrastructure. Our surveys received 299 responses and respondents reported risk-taking behaviours such as pavement riding, alcohol consumption, and minimal helmet use. However, positive opinions were expressed on e-scooter convenience but concerns were raised regarding rider and non-rider safety.DiscussionWhilst global literature had investigated e-scooter attitudes, risk-taking behaviours and perceptions, there was no comparable independent United Kingdom literature. Our literature review and analysis of survey responses concluded that e-scooters were perceived as a sustainable form of transport; however, safety concerns were raised. Our study points to risk-taking behaviours by riders being associated with admissions into hospital emergency departments. We conclude that well maintained infrastructure could improve the safety of both e-scooter riders and vulnerable pedestrians, whilst education and enforcement of clear rules may reduce risk-taking behaviour. The recommendations found in the PACTS reports, and documents from the RNIB confirm our findings. We recommend that hospital data and future studies should differentiate between private and rental e-scooters for robust conclusions to be made.